PERAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DALAM MEMPERKUAT CADANGAN DEVISA NEGARAMELALUI EKSPOR - Hugo Aries Suprapto (JABE (Journal of Applied Business and Economic), 2015)
The global era  currently pushed the stage to the country?s to pay attention to world trade. Spare exchange was a clean position asset  a broad governments assets that can be produced from UMKM. Foreign exchange reserves is important for a country and its position fluctuated. There for it is necessary to test the several factors that can affect the country?s foreign exchange reserve position that exports carried by UMKM. This research aims to determine the effect of exports to foreign exchange reserves. The analysis used multiple linear regression and processed using SPSS 20. The result showed  there is significant and positive influence of export to foreign exchange reserves. That mean, if exports up to, the country?s foreign exchange reserves increase.